MENANGKAL RADIKALISME MELALUI PENDIDIKAN AGAMA ISLAM BERBASIS ASWAJA NAHDLATUL ULAMA’ - Muhammad Husnur Rofiq; Riza Ahmad Ridwan (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2019)
One education that can provide values in counteracting radicalism is Islamic education based on Nahdlatul Ulama. Because Nahdlatul Ulama 'based Islamic education gives more value to education. Nahdlatul Ulama-based Islamic education is flexible in dealing with a situation and condition that exists in society. This research method uses library research which analyzes problems from several books, journals, and relevant scientific publications. The results of this study indicate that the educational process to counteract radicalism is with the approach of Islamic religious education based on Nahdatul Ulama. community values are internalized so that they are tolerant (tasamuh) towards others or others.